Herbal Medicine for Women\'s Health - L Kashani; MR Nikbakhat; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2015)
The treatments used by most doctors are considered conventional medicine. Complementary and alternative medicine (CAM) consists of a group of health care practices and products that are considered out of the mainstream. An "out-of-the-mainstream" treatment is considered complementary if you use it along with conventional medicine. Research shows that 40 percent of women in the United States use some form of CAM. People try CAM for a variety of reasons, including: conventional medicine has not helped solve their medical problem. They believe that products derived from nature are healthier and safer than prescription drugs, even though they may not be. They like the holistic approach taken by CAM therapists. A holistic approach involves paying attention to all of a client's needs to help her regain and maintain her health. These include not just physical but also emotional, social, and spiritual needs. In this review we summarize some indications of herbal medicine in womenchr('39')s health.